2017
DOI: 10.3389/fnmol.2017.00078
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitination, Disaggregation and Proteasomal Degradation Machineries in Polyglutamine Disease

Abstract: Polyglutamine disorders are chronic, progressive neurodegenerative diseases caused by expansion of a glutamine tract in widely expressed genes. Despite excellent models of disease, a well-documented clinical history and progression, and established genetic causes, there are no FDA approved, disease modifying treatments for these disorders. Downstream of the mutant protein, several divergent pathways of toxicity have been identified over the last several decades, supporting the idea that targeting only one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 99 publications
0
30
0
Order By: Relevance
“…We speculate that these changes result in enhanced proteotoxicity, leading to muscle atrophy through distinct and currently poorly characterized mechanisms. The extent to which proteasome dysfunction occurs in the polyQ diseases has been controversial, as previous findings in vivo have lacked consistency and reproducibility (60). In SBMA, proteasome activity was previously studied in transgenic mice overexpressing AR97Q.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that these changes result in enhanced proteotoxicity, leading to muscle atrophy through distinct and currently poorly characterized mechanisms. The extent to which proteasome dysfunction occurs in the polyQ diseases has been controversial, as previous findings in vivo have lacked consistency and reproducibility (60). In SBMA, proteasome activity was previously studied in transgenic mice overexpressing AR97Q.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways are responsible for the clearance and degradation of misfolded and/or superfluous proteins. It stands to reason that these systems are somewhat compromised in SCA patients, and numerous studies have now shown that these systems do in fact exhibit impairment in SCA diseases [61][62][63][64][65]. The dysregulation is believed to play a role in protein aggregation, as the misfolded polyQ proteins are unable to be effectively degraded, which leads to an increased proportion of aggregates.…”
Section: Protein Aggregation: a Hallmark Featurementioning
confidence: 99%
“…The dysregulation is believed to play a role in protein aggregation, as the misfolded polyQ proteins are unable to be effectively degraded, which leads to an increased proportion of aggregates. These pathways are currently an obvious and attractive therapeutic avenue for SCA diseases [65,66].…”
Section: Protein Aggregation: a Hallmark Featurementioning
confidence: 99%
See 1 more Smart Citation
“…Among all the UPS components, E3 ub ligases have gained huge attention in polyQ disease pathogenesis studies (Nath and Lieberman ; Atkin and Paulson ). The E3 ub ligases are responsible for recognizing and recruiting target proteins for ubiquitination, and thus, they confer substrate specificity to UPS (Upadhyay et al .…”
mentioning
confidence: 99%